Measuring indian patients' satisfaction : a case of private hospitals - Ali, S. Samar (2010)
Exposure to global markets and competitors has placed increasing demands on all sectors of the Indian market. Introducing consumer choice was one of the key motivations underpinning the various healthcare utility privatization of the Indian Hospitals in 1980s, along with enhancing the quality of service provided to consumers. Customer satisfaction is becoming increasingly important for organizational survival, let alone prosperity. This paper aims to study the effect of service facilities provided to patients in private hospitals of India. Suitable satisfaction drivers are identified from the literature and talks with experts. A new customer satisfaction index is discussed. This index is based on American Customer Satisfaction Index (ACSI}. The concept is developed specially for the private hospitals operating in New Delhi and NCR market of India. A survey was carried out and 180 responses were collected. Application of factor analysis for satisfaction drivers shows that these variables are well represented by four dimensions, viz. information, process, service and expectation. From the point of view of the user, an advantage of the new customer satisfaction index, which can be named the Patients Satisfaction Index (PSI}, is that the values of the coefficients of the satisfaction drivers give clear hints on potential improvements for researchers and practitioners